The long-term effect of social, educational, and health expenditures on indicators of life expectancy: an empirical analysis for the OECD countries - Aytemiz, Levent; Sart, Gamze; Bayar, Yilmaz; Danilina, Marina; Sezgin, Funda H. (Frontiers in Public Health, 2024)
Life expectancy provides insights into population health and the socio-economic development level of a country. However, there has been a significant gap in life expectancy between developed and underdeveloped countries, although these countries and international institutions have focused on reducing these inequalities. This article explores the long-term effects of social, educational, and health expenditures together with GDP per capita on indicators of life expectancy in the OECD states over the period of 2005–2021 through second-generation cointegration analysis. The results of the cointegration analysis demonstrate that public social and educational expenditures, health expenditures, and real GDP per capita have a positive effect on indicators of life expectancy in the OECD states over the long term, but the effect of real GDP per capita and health expenditures on indicators of life expectancy is relatively higher than effect of public social and educational expenditures on indicators of life expectancy. In conclusion, the effective use of governmental resources in terms of social, educational, and health expenditures can be beneficial in improving population health directly and indirectly through economic growth and development.